Therapeutic effects of polysaccharides extracted from Porphyra yezoensis in rats with cerebral ischemia/reperfusion injury - Sun, Changjiang; Wu, Feng; Chen, Dandan; Ge, Jianbin (Archives of Biological Sciences, 2018)
The polysaccharides of Porphyra yezoensis (PPY), porphyrans, are recognized as the major active components as they have several biological properties. This study was performed to assess the effect of PPY administration against cerebral ischemia-reperfusion injury (IRI). Thirty-two adult Sprague-Dawley (SD) rats were chosen and divided into 4 groups as follows: group I – rats received only saline; group II – subjected to middle cerebral artery occlusion (MCAO) for 60 min followed by 24 h of reperfusion (IRI-induced); group III – pretreated with PPY (100 mg/kg) for 7 days, followed by IRI induction; group IV – treated with PPY (100 mg/kg) for 7 days without IRI induction. All the data were analyzed by Dunnett’s (multiple comparisons) test using SPSS software. Pretreatment with PPY significantly (p<0.01) lowered the neurological deficit and cerebral infarct volume in comparison with IRI-induced rats. A pronounced (p<0.01) increase in the levels of antioxidant components (superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GSH)) was observed in PPY-supplemented rats. Also, the proinflammatory markers: interleukin-1β (IL-1β), interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α) and the nuclear factor-kappa B protein, subunit p65 (NF-κB p65) were substantially (p<0.01) suppressed in PPY-administered rats. Moreover, the protein levels of TNF-α and NF-κB p65 were considerably (p<0.01) downregulated upon pretreatment with PPY. Our data suggest that PPY could exhibit neuroprotective activity by attenuating oxidative stress and the inflammatory response. https://doi.org/10.2298/ABS170621039S Received: June 21, 2017; Revised: October 8, 2017; Accepted: October 8, 2017; Published online: October 16, 2017 How to cite this article: Sun C, Wu F, Chen D, Ge J. Therapeutic effects of polysaccharides extracted from Porphyra yezoensis in rats with cerebral ischemia/reperfusion injury. Arch Biol Sci. 2018;70(2):233-9.